Prevalence of Co-morbidities and Severity of COPD. (4th July 2015) - Battaglia, Salvatore; Basile, Marco; Scichilone, Nicola; Bellia, Vincenzo
Abstract We aimed at exploring whether the prevalence of co-morbidities of chronic obstructive pulmonary disease (COPD) increases with COPD severity. Analysis of medical records of outpatients with established diagnosis of COPD was retrospectively performed. The lower limit of normality (LLN) for FEV1/FVC was applied to establish the occurrence of airway obstruction in the elderly population. The prevalence of co-morbidities was calculated, and the proportion of patients with each co-morbidity along with GOLD stages was analysed by chi-square for trend. A total of 326 (M/F: 256/70) consecutive outpatients with COPD (stage GOLD I to IV), aging 71.8 ± 9.2 years, were included in the analysis. The most frequent co-morbidities in the entire sample were systemic hypertension (64.7%), diabetes (28.5%), coronary artery disease (19.9%), arrhythmias (16.6%) and congestive heart failure (13.8%). Underweight patients were 8.0% of the sample while obese patients were 22.4%. None of the analyzed co-morbidities showed a trend towards increasing prevalence with COPD severity, except for nutritional problems. The current findings suggest that the occurrence and prevalence of co-morbidities is independent from the COPD severity, and encourage to assess co-morbidities even in the early stages of the COPD.